Effect of carbonation on leachability, strength and microstructural characteristics of KMP binder stabilized Zn and Pb contaminated soils. (February 2016) - Du, Yan-Jun; Wei, Ming-Li; Reddy, Krishna R.; Wu, Hao-liang
Abstract: This study presents a systematic investigation of effects of carbonation on the contaminant leachability and unconfined compressive strength of KMP stabilized contaminated soils. A field soil spiked with Zn and Pb individually and together is stabilized using a new KMP additive under standard curing conditions and also with carbonation. The KMP additive is composed of oxalic acid-activated phosphate rock, monopotassium phosphate and reactive magnesia. The stabilized soils are tested for acid neutralization capacity, toxic characteristics leaching characteristics, contaminant speciation and unconfined compression strength. X-ray diffraction, scanning electron microscope and energy dispersive spectroscopy analyses are performed to assess reaction products. The results demonstrate that carbonation increases both acid buffer capacity index and unconfined compressive strength, but decreases leachability of KMP stabilized soils. These results are interpreted based on the changes in chemical speciation of Zn and Pb and also stability and solubility of the reaction products (metal phosphates and carbonates) formed in the soils. Overall, this study demonstrates that carbonation has positive effects on leachability and strength of the KMP stabilized soils. Highlights: Carbonation increased acid neutralization capacity of KMP stabilized soils. Carbonation lowered leached Zn and Pb concentrations and increased strength. Carbonation increased reducible and residual fractions of contaminants. Metal phosphate and carbonate products improved leaching/strength characteristics.